Compensation for aircraft effects of magnetic gradient tensor measurements in a towed bird. Issue 5 (1st October 2018) - Xiu, Chunxiao; Meng, Xiaohong; Guo, Lianghui; Zhang, Sheng; Zhang, Xingdong
Abstract : The effect of magnetic interference from the helicopter on full gradient tensor measurements acquired in a towed bird is substantial and must be corrected if airborne data are to be usable. During the actual flight process, the helicopter's and bird's attitudes, as well as the relative position between the helicopter and bird, change continuously. Thus the traditional method of compensation for aircraft effects is not suitable for this mode of measurement. For a particularly long towline, magnetic interference from helicopter can be reduced, but the errors introduced by substantial variations in altitude and orientation of the bird may be even greater than the magnetic interference from the helicopter. We have developed a compensation model from the perspective of forward modelling to correct full gradient tensor data measured in a towed bird for the magnetic effects of the helicopter, taking into account variations in attitude of the bird and helicopter. We designed training flight projects that allow compensation parameters to be estimated. The feasibility of the compensation method was verified by modelling and simulated flight tests. Finally, this method was applied to real data and the data quality was improved. Abstract : We present a compensation model of aircraft effects for full magnetic gradient tensor data acquired in a towed bird. Training flight tests were designed so that aircraft compensation parameters could be estimated. The feasibility of the compensation method was verified by modelling and by a flight simulation test.